2008
DOI: 10.1080/09637480701453553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fully and partial substitution of NaCl by KCl on physico-chemical and sensory properties of white pickled cheese

Abstract: White pickled cheeses were produced with different salting treatments, vacuum-packed in polyethylene containers, and stored at 4 +/- 1 degree C for 90 days. Five different concentrations of NaC1, KC1 or NaCl/KCl mixtures (sample A, 100% NaCl; sample B, 100% KCl; sample C, 75% NaCl + 25% KCl; sample D, 50% NaC1+50% KCl; sample E, 25% NaCl+75% KCl) were applied in the production of cheeses. Some physical, chemical and sensory properties of the samples were monitored at 0, 15, 30, 60 and 90 days of ripening. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 18 publications
4
21
1
2
Order By: Relevance
“…In addition, Al‐Otaibi and Wilbey reported no significant differences between salt treatments for the sensory scores of salty taste as obtained in the present work. Higher bitterness ratings for brine B samples were also obtained by Karagözlü et al and Gomes et al Both higher hardness and bitterness levels could have a negative impact on acceptability, especially if excessive. In a similar finding, Ayyash et al reported that no significant differences were observed in creaminess, saltiness and sour‐acid among Akkawi cheese for the same storage period.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In addition, Al‐Otaibi and Wilbey reported no significant differences between salt treatments for the sensory scores of salty taste as obtained in the present work. Higher bitterness ratings for brine B samples were also obtained by Karagözlü et al and Gomes et al Both higher hardness and bitterness levels could have a negative impact on acceptability, especially if excessive. In a similar finding, Ayyash et al reported that no significant differences were observed in creaminess, saltiness and sour‐acid among Akkawi cheese for the same storage period.…”
Section: Discussionsupporting
confidence: 54%
“…Karagözlü et al reported that acidity of white pickled cheese increased significantly with decreasing levels of NaCl. However, opposite results were obtained by Ayyash and Shah, who reported significantly lower pH for cheeses stored in control brine (100% NaCl) than those stored in brines formed of NaCl and KCl mixtures, which was attributed to the higher pH of KCl compared to NaCl.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Simple salt reduction has been found to increase bitterness and decrease shelf‐life in cheeses, whereas partial salt substitution especially with KCl did not significantly affect cheese quality compared with the control (Guinee 2004b). Those authors have reported that cheeses made with partial NaCl substituted with KCl showed similar characteristics to those with the control (only NaCl) (Katsiari and others 1997; Karagozlu and others 2008; Ayyash and Shah 2010, 2011b). On the other hand, several studies have shown that partial substitution of NaCl with KCl affected the activity of proteolytic enzymes produced by starter cultures (Armenteros and others 2009; Ayyash and Shah 2011a, 2011d).…”
Section: Introductionmentioning
confidence: 83%